Culturally Informed Care: Solidarity, Cultural Humility, and Medical Ethics - Hawkins, Hailey; Nortjé, Nico; Palmer, Amitabha (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
This case study explores the ethical complexities surrounding the treatment of Mrs. H, an elderly woman with multiple myeloma. Divergent goals between her family, rooted in cultural and religious values, and the medical team prompted ethical deliberation. The divergent goals centered around the family’s desire for aggressive cancer treatment, driven by their Ubuntu and Christian beliefs in the sanctity of life and hope for divine intervention, contrasted with the medical team’s focus on palliative care, prioritizing comfort over aggressive medical interventions with unlikely benefits. Faced with this tension, the care team, guided by principles of solidarity and cultural humility, engaged in meaningful dialogue facilitated by an experienced ethicist. The resolution respects the family’s cultural and religious beliefs while adhering to medical ethics. This case highlights the importance of understanding and integrating cultural values in healthcare decision-making, ultimately achieving a patient-centered approach that respects the diversity of perspectives.